Beyond the Classroom: Leveraging International Community Service to Fortify Islamic Identity in Japanese Muslim Children - Khasanah, Nur; Ghufron, M. Ali (Society : Jurnal Pengabdian Masyarakat, 2025)
This community service focused on strengthening the Islamic character education of Muslim children within Japanese families through a series of highly interactive activities. The program was structured around practical engagement, including seminars, communal prayers, and targeted Quran recitation sessions. These components were specifically designed to deepen the children's grasp of core Islamic values and actively cultivate their religious practices. The results following the program were noteworthy. Data indicated a significant boost in the participants’ understanding of Islamic character, marked by a 30% increase in comprehension. Furthermore, there was a 25% rise in their active engagement with religious practices. Beyond the statistical improvements, a crucial, lasting outcome was the successful establishment of a supportive community network. This network now provides a vital lifeline for Muslim families in Japan, helping them navigate their daily lives while securely maintaining their cultural and religious identity. This program's success underscores its critical importance for ensuring the continued development of Islamic character among the younger generation in Japan, directly addressing the unique cultural and societal challenges they face. The findings strongly affirm that interactive and hands-on methods are essential for effective character education, pointing to a clear need for sustained support and the expansion of similar programs to benefit more Muslim families across the country.